Stability Analysis of Dike Pond Due to Pore-Water Pressure Changes - Agung, P. A. Maha; Hasan, Muhammad Fathur Rouf; Yatmadi, Denny; Susilo, Adi; Sutikno; Osa, Dominggus Benyamin; Adinegara, Aldo W.; Razi, Mohd Adib Mohammad; Ahmad, Mustaffa A.; Zainorabidin, Adnan (Salehan Institute of Higher Education, 2025)
The Brigif retention pond not only serves to temporarily store rainwater for groundwater reserving but also reduces the risk of flooding in the Southern Jakarta area. Research was purposed to study two critical conditions of a dike made from clayey material from before to after water impounding stages correlating with its stability. The research will investigate pore-water pressure (u) parameter changes at any stage in both conditions. The parameter of (u) can be predicted (upre) using the laboratory consolidation or oedometer test and measured (uact) completely with hydrostatic pressure (u0) directly in the field. Actual measurements using a piezometer were also conducted on the body of the dike. The prediction analysis used the self-developed program and conventional geotechnical software. The critical peak depth of (u) was found at 3.0 to 4.0 m. The actual settlement potential values reached -0.10 to -1.42 m and matched the prediction result. Safety factor (SF) was around 2.0 to 4.0, or in stable condition. Research results found that the magnitude parameter of (u) could be influenced by groundwater flow and porosity or void ratio fluctuations. The consolidation process also would affect the physical soil pore, contributing to the change of (SF) the dike pond.